Hubungan indeks massa tubuh dengan tingkat kebugaran kardiovaskular pada mahasiswi Program Studi Pendidikan Dokter, Fakultas Kedokteran Universitas Udayana usia 18-21 tahun - Kadek Dwi Pradnya Andrastea; I Nyoman Mangku Karmaya; I Nyoman Gede Wardana (Bali Anatomy Journal, 2018)
Background: Cardiovascular fitness is defined as the ability of the heart, lungs, and blood vessels to provide oxygen for muscle work during rhythmic and continuous activities. An increase in body mass index (BMI) is a major risk factor for a decrease in cardiovascular fitness. According to the 2013 Basic Health Research (Rikesdas) data, the prevalence of obesity in Indonesia is increasing in adults (≥18 years), especially in women. Method: The design of this study was analytic observational with the cross sectional approach. The sample consisted of 84 female students of Medical Education Study Program in Medical Faculty of Udayana University, aged 18-21 years old, calculated by the formula for correlation test. The samples were collected by a simple random sampling method. The height of each sample was measured by microtoise, the body weight was measured by manual weighing scales, while the Harvard step test measured cardiovascular fitness. The relationship between BMI and cardiovascular fitness level was analyzed by hypothesis test and Spearman correlation test. Results: While 33.33% of respondents in this study fell into the obesity group (BMI ≥ 23 kg / m2) and 55.95% were included in weak cardiovascular fitness category (Harvard score <83). The results of the Spearman correlation test showed a p-value of ≤ 0.05 and r = -0.444 which presented a moderate and significant negative relationship between BMI and cardiovascular fitness. Conclusion: There is a significant relationship between BMI and cardiovascular fitness among female students of Medical Education Study Program in Medical Faculty of Udayana University aged 18-21 years old, in which with increasing BMI value there’s a decrease of cardiovascular fitness.